Are strategy researchers worse strategy teachers in business schools? - Santaló, Juan; Moschieri, Caterina (IE University, 2019)
In this study we examine whether in business schools a professor’s research quality impacts her performance in the classroom. We build a novel dataset of students’ teaching evaluations of 922 strategic management courses in a top-ranked business school in Spain in the period 2011-2016 linking it to the publication outcome of each professor. We find a significant positive association between research quality measured by the sum of the number of publications in a six-year interval and students’ evaluations of teaching. Specifically, we find that an increase of two standard deviations on our variable of research quality is associated to an increase in students’ evaluations equivalent to the jump from being a median professor to being in the top quartile of best performers in class. Moreover, we find that a professor with four publications in a six year period increases the likelihood of her students choosing strategy elective courses up to 21.5 percent. We also find a positive and strongly significant interaction of research quality with course length, suggesting that the benefits of research may emerge specifically in longer courses. These findings extend the current discourse on the impact of research on teaching to strategic management courses in business schools.Financiado por parcialmente: Ministerio de Economía, Industria y Competitividad Título: How do institutional forces shape firms' strategic decisions? Acrónimo: IFS Numero: ECO2016-77205-P
Keywords: Business schools;Strategic management;Students evaluations;Teaching; Business schools; Strategic management; Students evaluations; Teaching; 58 Pedagogía::5802 Organización y planificación de la educación; ODS 4 - Educación de calidad